Roma community-based empowerment does matter! A qualitative study of social workers' experiences with the empowerment process of social workers in central Slovakia - Kozubík, Michal; Tokovska, Miroslava; Hricová, Alena; Šolcová, Jana; Hanková, Magdalena; Minarovičová, Katarína; Nováková, Radana (Kontakt, 2025)
This qualitative study examines the implementation of an empowerment approach in marginalised Roma communities from the perspective of social workers. Data from 11 semi-structured interviews were analyzed using selected analytical procedures of grounded theory, identifying the main categories: the socioeconomic background of clients (context), community needs and long-term goals (causal conditions), social support and external influences (intervening conditions), and educational projects and participation (strategic actions). The empowerment process leads to independence, sustainability, and improvement of the community environment (consequences). While social work at the micro and meso levels is crucial for the inclusion of the poorest residents of segregated Roma enclaves, significant achievements have not been made at the macro level, particularly in terms of political involvement and the fight against anti-Roma racism. The study also highlights systemic reliance on European structural funds and the lack of state support. Future research could map the perspectives and empowerment of emerging helping professionals.
Keywords: Empowerment; Minority Health; Roma; komunitní participační výzkum; Social Workers; sociální pracovníci; Community-Based Participatory Research; Qualitative Research; Slovakia; lidé; Slovenská republika; zdraví menšin; Romové; kvalitativní výzkum; empowerment; Humans